Penerapan e-system perpajakan PPh Pasal 25 di KPP Pratama Kota Manado - Mamadoa, Novalinda Jesika; Wangkar, Anneke; Kindangen, Wulan Deisy (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to determine the implementation of e-system for PPh Article 25 taxation at KPP Pratama Manado. The study was conducted at the Manado Pratama Tax Service Office. The types of data used in the study were primary data and secondary data. This study used qualitative descriptive analysis techniques. The results of the study indicate that (1) The implementation of e-system for taxation for receiving PPh Article 25 at KPP Pratama has been quite effective, (2) Its implementation for individual taxpayers has not been effective because there are still taxpayers who are confused about how to operate the system. This study is expected to provide information about e-system taxation that makes it easier for taxpayers to carry out their tax obligations.